2016
DOI: 10.1111/eea.12509
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic fractionation with morphological change and sexual specificity in the lappet moth Euthrix potatoria

Abstract: The δ15N values of adult holometabolous insects exceed those of larvae, but otherwise little information on terrestrial invertebrates has been obtained in food‐web analyses using stable isotope ratios (δ15N, δ13C). Changes in δ13C during metamorphosis and differences between males and females have not been examined. We collected the larvae and cocoons of Euthrix potatoria (L.) (Lepidoptera: Lasiocampidae) in the field and used them to assess the species’ isotopic fractionation. Each emerged moth was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Considering the Δ 15 N values, only δ 15 N enrichment was observed in all treatments, which is expected with the increase of trophic level [10, 43] (S2 Table).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the Δ 15 N values, only δ 15 N enrichment was observed in all treatments, which is expected with the increase of trophic level [10, 43] (S2 Table).…”
Section: Resultsmentioning
confidence: 95%
“…For instance, Hood-Nowotny et al [23] observed differences in the δ 13 C signals between males and females of C . capitata reared on artificial larval diets, and Sato and Azuma [43] detected significant differences in δ 13 C of males and females of Euthrix potatoria L. However, such differences were not large enough to preclude the use of stable isotope as markers of flies reared in laboratory [23]. Future analyses of specific body structures instead of whole body could help to elucidate the existence of any differences in isotopic signatures between sexes of A .…”
Section: Discussionmentioning
confidence: 99%
“…Balagawi et al (2014) found no differences in total body nitrogen or carbon for both sexes of wild Bactrocera tryoni (Froggatt) (Diptera: Tephritidae). In contrast, some researchers have observed sex-associated variations in δ 13 C signatures, especially when females present a higher storage of lipids, which are generally depleted in 13 C relative to bulk biomass (Hayes 2001;Hood-Nowotny et al 2009;Sato & Azuma 2016). This is the first attempt to observe the turnover of carbon in A. fraterculus adults by switching the carbon stable isotope composition of diets.…”
Section: Treatmentmentioning
confidence: 88%
“…However, when using stable isotope analysis to estimate insect diets, selection of the appropriate developmental stage is crucial to avoid false conclusions. In the case of holometabolous insects such as butterflies, adult tissues are often enriched in 15 N relative to larval tissues due to isotopic fractionation during metamorphosis [47, 49, 50]. Without knowledge of the size of this fractionation in A. usamba , the observed enrichment in 15 N in A. usamba adults was interpreted as a shift in trophic position, when it is more likely to have been an artifact of ontogenetic changes.…”
Section: Discussionmentioning
confidence: 99%